2008
DOI: 10.1002/j.2050-0416.2008.tb00318.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Heavy Metal Ions on Beer Flavour Stability

Abstract: In this study, the importance of iron and copper ions and their radical formation via the respective Fenton and Haber-Weiss reactions was confirmed. Of the other heavy metals present in the brewing process in relevant concentrations, the impact of manganese ions on beer flavour stability has been elucidated. In contrast to iron and copper, manganese ions are not removed from wort or beer to any great extent during the process. Additionally, manganese shows a similar radical-promoting effect to that seen with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 10 publications
5
48
0
2
Order By: Relevance
“…Fe, Mn 2+ ) negatively impact the process, inducing free radical formation (7), which results in a deterioration of flavour during storage (3). The metal ion content of the wort depends mainly on the quality of the raw materials (barley malt, water and hops).…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Fe, Mn 2+ ) negatively impact the process, inducing free radical formation (7), which results in a deterioration of flavour during storage (3). The metal ion content of the wort depends mainly on the quality of the raw materials (barley malt, water and hops).…”
Section: +mentioning
confidence: 99%
“…The ionic composition of brewer's wort is an important factor that influences the fermentation process and beer quality (1)(2)(3). Some ions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed, however, that even in the absence of lipoxygenase, unsaturated fatty acids can be degraded through the action of reactive oxygen species 20 . Oxygen activation is effected by metal ions, notable iron and copper 18 , although it has recently been suggested that manganese, derived from malt, may be at least as relevant 168 . Irrespective of whether oxidation of unsaturated fatty acids is enzyme-driven or non-enzymic, the minimization of oxygen levels in the mash would be beneficial.…”
Section: Flavour Instabilitymentioning
confidence: 99%
“…They are active in both anaerobic and aerobic environments, but their effectiveness is higher under aerobic conditions. Activation of oxygen by metal can also support OFR formation (12,13).…”
Section: Introductionmentioning
confidence: 99%